Acute Kidney Injury in Patients with Sepsis and Septic Shock: Risk Factors and Clinical Outcomes - Suh, Sang Heon (Yonsei University College of Medicine, 2013)
PURPOSE: The aim of this study was to investigate clinical characteristics and risk factors of acute kidney injury (AKI) in patients with sepsis and septic shock. Additionally, we explored whether the severity of AKI affects on the clinical outcomes. MATERIALS AND METHODS: Data were collected retrospectively in a single center. Among 5680 patients who visited emergency department from January to December 2010, 992 patients with sepsis and septic shock were enrolled. Patients were divided into two groups, patients who developed AKI or not, to compare the baseline characteristics, and laboratory and physiologic data. Patients with AKI were subdivided according to its stages for survival analysis. RESULTS: AKI was developed in 57.7% of patients. Multivariable logistic regression analysis revealed that development of septic AKI was associated with older age, pre-existing chronic kidney disease, use of angiotensin converting enzyme inhibitor or angiotensin receptor blocker, presence of shock, positive blood culture results, and low white blood cell and platelet counts. Hospital mortality was higher in AKI group. Crude Kaplan-Meier survival curves demonstrated reduced 30-day survival rate was significantly associated with the severity of acute kidney injury. CONCLUSION: The development of septic AKI was associated with poor clinical outcomes. Furthermore, the severity of AKI was associated with increased mortality.